A research on the factors affecting treatment seeking behavior of Turkish originated heroin dependents in germany - Yalnız, Özlem; Pektaş, Özkan; Şahin, Emre; Kalyoncu, Ö. Ayhan; Mırsal, Hasan; Beyazyürek, Mansur (Journal of Dependence, 2004)
Objective: A multitute of factors influence treatmentseeking behaviour in heroin dependence. The aim of this study was to investigate sociocultural characteristics and clinical features influencing the decision of our inpatients who were Turkish originated heroin dependents living in Germany and preferred to seek treatment in Turkey. Methods: This study included 98 Turkish originated heroin dependents living in Germany who met the diagnostic criteria of heroin dependence according to DSM-IV and who applied for hospitalization. A semi-structured test with 76 items was conducted to all patients. In this study, the evaluated variables were sociodemographic data, cultural characteristics, family information, cultural adaptation, causes of migration, methods of heroin use, the way of obtaining heroin, legal problems, presence of imprisonment, treatmentseeking behaviour and consequences. All of the data were analyzed by SPSS (Windows 10.0) program. Results: The sample of this study included 8 female (8.2%), 90 male (91.8%) patients . The mean age of the patients was 28.7 (ss = 7.8) years. The age of starting heroin use was under 20 years (85.7%). In the study group, 37.7% of all patients used heroin by injection. The study group reported that heroin use was common in their peer group. In the study group 87.8 % of all patients had legal problems and 46.9% of all patients reported a history of imprisonment due to heroin use. Conclusion: The results show that sociocultural factors play an important role on the decision of Turkish originated heroin dependents in Germany to seek treatment in Turkey. Multicenter, controlled and transcultural oriented studies are further needed.